Project risk management in Malaysian oil and gas industry: Implementation by EPC local Contractor / Zaim Aiman Che Rosli - Zaim Aiman, Che Rosli (2020)

(untitled)
The megaproject in Downstream Sector of Oil and Gas Industry only achieve 50% success rate which warrants attention by researchers. The Owners and Contractors are not fully aware on the full range of project risks and only few have demonstrated the knowledge and expertise in managing risk effectively. The common understanding had by the EPC Contractor is they are having the full flexibility and freedom in performing execution work by maximizing profit while still complying towards client’s requirement as the contract price has been fixed during award stage. However, there is a hidden risk which seldomly being placed attention by the higher management after the project been awarded to the winning EPC Contractor. Therefore, studies are needed to increase the understanding of recurring risks in the EPC projects and the risk management applied by the Oil and Gas Company. However, limited studies have been performed in Malaysia Oil and Gas Industry. This research attempts to investigate project risk management implementation by EPC Local Contractor within Downstream Sector of Malaysian Oil and Gas Industry by providing the necessary recommendation for Oil and Gas Regulator for improvement towards the risk management practices during execution phase. Data was obtained from thirty-three respondents via quantitative method and the distributed through online survey. The study revealed that there is a sufficient awareness on risk management practices from Organization and Project Team in the EPC Local Contractor and sufficient understanding on the benefit towards project performance. However, there is a gap on the risk management process based on this study towards the last process. The study also found the differences in the limitations and barriers towards an effective risk management when compared with other industry for the case of Malaysia Oil and Gas. iv Three (3) recommendations were proposed for consideration by the Regulator of Malaysia Oil and Gas Industry from this study which are (1) Training and Capability Development, (2) Refinement towards requirement of risk management during tendering and (3) Selection of right Project Management Standard and Risk-Based Strategy from complexity assessment. Recommendation concluded from this study can act as a reference points by Regulator of Malaysian Oil and Gas Industry in enhancing the current risk management framework for a continuous improvement. Keyword: Malaysia, Oil and Gas Industry, Risk Management, EPC Local Contractor